SPIRITUAL WELL BEING WITH QUALITY OF LIFE IN DIABETES MELLITUS PATIENT IN WORKING AREA TANJUNGANOM HEALTH CENTER OF NGANJUK REGENCY - Ardiansyah, Ganda; Purwandari, Henny; Wahyuni, Ririn Tri (Journal of Vocational Nursing, 2020)
Introduction: Physical and psychological problems in Diabetes Mellitus patient can affect quality of life. Good quality of life can help Diabetes Mellitus patient manage disease and maintain good health. Spiritual well being is associated with individual coping patterns and self care behavior of Diabetes Mellitus patient who can improve quality of life. The purpose of this research is to know the relation of spiritual well being with quality of life in Diabetes Mellitus patient in working area Tanjunganom Health Center of Nganjuk Regency. Methods: The research was conducted on 1 February 2018 and 18 March 2018 in auxiliary Health Center Jogomerto, auxiliary Health Center Surodadi and auxiliary Health Center Sumberkepuh. Correlation study design with crosssectional approach. The population was Diabetes Mellitus patient in working area Tanjunganom Health Center of Nganjuk regency with total 61 people. A sample of 27 respondents, the sampling technique was cluster random sampling. The independent variable was spiritual well being and the dependent variable was quality of life. Data collection using Spirituality Well Being Scale and Diabetes Quality of Life questionnaires. Statistical test using Spearman Rank SPSS 16 with significance α = 0,05. Results: The result showed almost half of Diabetes Mellitus patient 13 respondents (48.1%) has spiritual well being medium and almost half were 12 respondents (44,4%) has medium quality of life. Spearman Rank test results obtained Ï value = 0,000 and r = 0.963 because Ï value â‰¤ α (α = 0,05) then Ha accepted and Ho rejected. Conclusion: The results showed there is a relation between spiritual well being with quality of life in Diabetes Mellitus patient in working area Tanjunganom Health Center of Nganjuk Regency. Spiritual approach through religious activities can be used as a strategy to improve spiritual well being, so as improve quality of life.